Virtual Reality in a shipbuilding environment. (March 2015) - Pérez Fernández, Rodrigo; Alonso, Verónica
Highlights: A natural consequence of the extended use of CAD systems for the design and production of any kind of vessel is its use in Virtual Reality environments. Virtual Reality is extended in every industry, in every sector, at any level. This paper describes different efficient uses of Virtual Reality in the shipbuilding industry, taking in consideration all the agents involved. A solution of Virtual Reality needs to be composed of the following components: a system display, helmet, a motion tracking system, computer, infrastructure and the software. Abstract: A natural consequence of the extended use of CAD systems for the design and production of any kind of vessel is its use in Virtual Reality environments, mainly because now it has become an accessible technology. Virtual Reality is extended in every industry, in every sector, at any level. Important improvements both in software and hardware have had an important impact in its use in the shipbuilding industry, where it is necessary to handle complex ship 3D models with huge amount of data. So, efficiency is the base condition in the Virtual Reality navigation around a vessel. To enhance it, there are three important factors that play a fundamental role. The first one is having an appropriate CAD system with all the information of the ship in a single data base. The second important issue is to have a viewer, which is a tool that allows the management of the 3D model to be used in Virtual Reality environments. No need to say that a good integration between the viewer and the CAD system will be translated into more functionality and better performance. Finally, the third important player is hardware, which makes possibility the Virtual Reality navigation in many different environments. This paper describes first of all different efficient uses of Virtual Reality in the shipbuilding industry, taking in consideration all the agents involved and describing in particular the advantages for any of them. Regarding the software requirements, it will be described in particular the new FVIEWER, developed by SENER for the Virtual Reality navigation and design review and based on the FORAN system. From the hardware side, it will be described some of the most relevant and feasible applications of the Virtual Reality, taking in consideration potential uses and accessible technology in the market. The future of the Virtual Reality in shipbuilding will be explained after that.